Horizontal equity in the German tax-benefit system: A simulation approach for employees - Timm Bönke; Sebastian Eichfelder (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
We analyze the distributive justice of the combined burden of taxes, social security contributions and public transfers on employee households. In order to investigate whether the treatment of families by the aggregate tax-benefit system can be regarded as 'fair', we compare the equivalent incomes of eight different household types. Using the concepts of system-inherent equivalence scales and horizontal equity we find evidence for a structural discrimination of low income families, while families in the high income brackets tend to be privileged. The equity in the treatment of a household type is not only affected by the amount but also by the distribution of income between the household members. Based on these results we can state a significant contradiction of value judgments within the German tax-benefit system. From the perspective of our paper, there is no convincing justification for this inconsistency.
Keywords: D31; D63; H24; 330; horizontal equity; family taxation; distributive justice; tax-benefit system; equivalent income; Steuerbelastung; Sozialtransfer; Privater Haushalt; Einkommensverteilung; Disparitätsmaß; Lebensstandard; Deutschland